Impact of the −174 G > C IL-6 Polymorphism on Bioelectrical Parameters in Obese Subjects after Laparoscopic Adjustable Gastric Banding - Laura Di Renzo; Maria Grazia Carbonelli; Alessia Bianchi; Emidio Domino; Maria Rita Migliore; Guido Rillo; Leonardo Iacopino; Nicola Di Daniele; Antonino De Lorenzo (Journal of Obesity)
Background. Recent data demonstrated that the −174 G>C IL-6 polymorphism may account for differences in the therapeutic response to laparoscopic adjustable gastric banding (LAGB) surgery. Objective. We investigated the impact of −174 G>C IL-6 polymorphism on weight loss, body composition, and fluid distribution changes in obese subjects after LAGB. Design and Outcome Measures. Twenty obese subjects were selected and studied at baseline and 3 months after LAGB. Genetic assessment of −174 G>C IL-6 polymorphism and anthropometric and bioelectrical impedance analysis were performed. Results. At baseline, C(+) carriers had a lower extracellular water (ECW) and higher intra-CW, phase angle (PA), reactance Xc, and Xc/height. LAGB surgery determined significant reductions in weight and BMI. After LAGB, in C(−) carriers, significant decreases in weight, BMI, and ECW and increases in BCM, BCMI, ICW, PA, and Xc/H were highlighted. In C(+) carriers, significant reductions in weight, BMI, ICW, and PA and increases in ECW, Na/K, resistance (R), and R/height were obtained. Significant higher reductions in BMI and Xc/H were observed in C(+) with respect to C(−) carriers. Conclusions. Genotyping of genetic variants, for example, the −174 G>C polymorphism of IL-6, gives the opportunity to predict therapeutic response, in terms of body composition outcomes after LAGB.